A survey on short-range WBAN communication; technical overview of several standard wireless technologies - Al_Barazanchi I.; Niu Y.; Nazeri S.; Hashim W.; Alkahtani A.A.; Shaheed H.R.A. (International University of Sarajevo, 2023)
In a healthy environment, a WBAN system is the key component or aspect of the patient monitoring system. WBAN systems allow for easy networking with other devices and networks so that healthcare professionals can easily access critical and non-critical patient data. One of the main advantages of WBAN is the remote monitoring of patients using an Intranet or the Internet. There are two main components to the type of communication technology used in WBAN. This page shows an insight of a variety of short-range standardized wireless devices, as well as a taxonomy of short-range technologies. These are proposed as intra-BAN communication candidates for communication within and between body area network (BAN) entities. This paper also highlights the advantages and disadvantages of the WBAN perspective. Finally, a side-by-side comparison of the basic principles of using MICS frequency bands and preparatory technologies. The Author 2021. This work is licensed under a Creative Commons Attribution License (https://creativecommons.org/licenses/by/4.0/) that allows others to share and adapt the material for any purpose (even commercially), in any medium with an acknowledgement of the work's authorship and initial publication in this journal.